Benign hereditary chorea, not only chorea: a family case presentation. Issue 1 (December 2016) - Koht, Jeanette; Løstegaard, Sven; Wedding, Iselin; Vidailhet, Marie; Louha, Malek; Tallaksen, Chantal
Abstract Background Benign hereditary chorea is a rare disorder which is characterized by early onset, non-progressive choreic movement disturbance, with other hyperkinetic movements and unsteadiness also commonly seen. Hypothyroidism and lung disease are frequent additional features. The disorder is caused by mutations of theNKX2-1 gene on chromosome 14. Case presentation A Norwegian four-generation family with eight affected was identified. All family members had an early onset movement disorder, starting before one year of age with motor delay and chorea. Learning difficulties were commonly reported from early school years. The family presented with choreic movements at rest, but other movements were seen; myoclonus, dystonia, ataxia, stuttering and tics-like movements. All patients reported unsteadiness and ataxic gait was observed in two patients. Videos are provided in the supplementary material. Most affected family members had asthma and a subclinical or clinical hypothyroidism. Sequencing revealed a mutation in theNKX2-1 gene in all eight affected family members. Conclusions This is the first Norwegian family with benign hereditary chorea due to a mutation in theNKX2-1 gene, c.671 T > G (p.Leu224Arg). This family demonstrates well the wide phenotype, including dystonia, myoclonus and ataxia.